Stellaria popovii, a new name in Caryophyllaceae - Pusalkar, Prashant K. (Phytotaxa, 2016)
As part of the ongoing study on the Western Himalayan Caryophyllaceae Juss. (see e.g., Pusalkar & Singh 2015, Pusalkar & Srivastava 2015, Pusalkar & Srivastava 2016), I came across to Stellaria fontana Popov (1936: 407) from lower Ladakh (Jammu & Kashmir, India; see Klimés and Deckore 2005). A careful check of the online nomenclatural databases (e.g., The Plant List 2013, IPNI 2015+) revealed that the Popov’s name is a later homonym of S. fontana Wulfen (1786: 327). As a consequence, it is illegitimate under the Art. 53.2 of ICN (McNeill et al. 2012). A new name—Stellaria popovii—is here proposed for S. fontana Popov.